UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA MATERI POKOK PESAWAT SEDERHANA MELALUI MODEL PEMBELAJARAN INDEX CARD MACTH (KARTU BERPASANGAN ) KELAS V SEMESTER GENAP DI SD NEGERI 2 BUNGATAN KABUPATEN SITUBONDO TAHUN PELAJARAN - Junaidi Junaidi; Putu Eka Suarmika (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2015)
The process of education and learning will work effectively if it is in a conducive, warm, fun, interesting and comfortable environment. Therefore, teachers should understand the various teaching strategies with their various characteristics, so as to be able to choose appropriate teaching strategies and be able to use them varying in accordance with the expected goals or competencies. The purpose of this study is to improve the activities and learning outcomes of learners through the Strategy of learning Index Card Match on science subjects basic subject of simple aircraft class V Even semester in SD Negeri 2 Bungatan Lessons Year 2013 / 2014.Desain this study is a model of Hopkins scheme with using 4 phases: planning, action / action, observation and reflection. To obtain data in this study using the method of observation, interview and test. Data analysis in this research use qualitative descriptive analysis. Based on the results of research on the implementation of the second cycle of student activation observation indicates an increase. It can be seen on student activity which has a high enough increase compared to observation conducted in cycle I that there is an increase of 6,25% that is 84,52% at student activity observation cycle I to become 90,77%. While the results of student learning at the meeting cycle II obtained data 4 students who are not complete from 28 students who follow the daily test, because the students score less than 70 from a score of 100 and 24 students have completed in the classical reach 85.71% and students are not complete 14.29%. Student learning outcomes in cycle II have improved quite well when compared with before the action and cycle I. Based on the results of research and analysis of the discussion that has been done, it can be concluded that: Implementation of Learning Strategy Index Card Match can Increase Activity and learning outcomes on science subjects simple subject matter plane at SD Negeri 2 Bungatan Lesson Year 2013/2014.